Abb. 5: Editor-Ansicht im J-Quizmaker - Rolf Schulmeister (FernUniversität Hagen, 2017)
Comparisons show online courses to be inferior to blended learning courses. Studies of the absence of students from classes as well as time budget analysis of the workload of Bachelor students provide evidence for a positive effect of the face-to-face component of blended learning environments on learning success. Attendance or presence seems to be even more important for the learning success than self-study, which in today's bachelor curricula with their conservative structure and classical teaching methods reduces learning to cramming. This essay presents some evidence for a special role of attendance for learning success and explains the positive effect of face-to-face (f2f) situations through motivation and communication theory, and an analysis of recorded lectures.